Interdisciplinary connections as a means of forming practice-oriented digital mathematical competence of technical university students - Badak, Bazhena A. (University Pedagogical Journal, 2025)
The article considers interdisciplinary connections as one of the key tools for the implementation of practice-oriented digital mathematical competence of students of a technical university. In a rapidly changing technological world, special attention is paid to the integration of knowledge from various disciplines to form students’ skills necessary for successful professional activity. The author describes the experience of introducing interdisciplinary, systemic and competence-based approaches into the educational process in order to develop critical thinking among students and master their methods of solving professionally oriented tasks. The results of the conducted pedagogical experiment show that interdisciplinary connections contribute to a deeper assimilation of mathematical concepts, methods and ways of their application in engineering practice, increasing the level of students’ readiness for real challenges in their future profession.